PENGARUH SISTEM FILTRASI TERHADAP KUALITAS DAN STABILITAS PRODUK LIQUID GLUKOSA PADA MESIN PLATE TYPE HERMETIC FILTER DENGAN DI PT. XYZ Tbk - Mochammad Arya Maulana; Wisma Soedarmadji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Filtration is an important separation process in various industries that produce liquid products. This process aims to remove suspended solid particles from liquids in order to obtain products with better clarity and quality. One of the filtration devices widely used in industry is the Plate Type Hermetic Filter, which operates in a closed system to minimize contamination from the external environment.This study aims to determine the effect of the filtration process on the quality and stability of liquid products using a Plate Type Hermetic Filter machine. The research method used in this study is an experimental method by conducting direct testing on the filtration process with several variations of operating parameters such as filtration pressure and filtration time. The parameters analyzed in this study include product clarity, suspended particle content, and product stability during the storage period. The data obtained from the experimental process were analyzed to determine the relationship between filtration conditions and the resulting product quality. The results show that the filtration process using the Plate Type Hermetic Filter machine is able to improve product clarity and reduce suspended particles in the liquid. In addition, optimal filtration also contributes to improving the stability of liquid products during storage. Therefore, an appropriate filtration process can enhance the quality and shelf life of liquid products in industrial processes